Development of Local Wisdom in Preventing Stunting in Village Communities - Sumardino, Sumardino; Lestari, Siti; Widodo, Widodo (JKG (JURNAL KEPERAWATAN GLOBAL), 2024)
Background: Child stunting refers to a child who is too short for his or her age and is the result of chronic or recurrent malnutrition, based on the height-for-age index (HAZ). The results of weighing and measurements at the Posyandu, or community health post, show an increase in the prevalence of stunting from 7% in 2019 to 10.41% in 2020. A preliminary survey at the Ceper Community Health Centre in Klaten Regency showed that out of 1,922 children under five, 187 were stunted. Local wisdom is considered highly valuable and has its own benefits for the lives of the community. Thanks to local wisdom, they can sustain their lives and even develop sustainably. The role of midwives in developing local wisdom for stunting prevention is crucial, as they are the frontline health workers in the prevention of stunting. Methods: The research design is an analytical observational study with a cross-sectional approach. Data analysis was conducted using regression. The research sample was taken using cluster random sampling techniques involving 60 respondents. Results: The data analysis results showed a relationship between the role of educators and motivators in the intervention of developing local wisdom for stunting prevention. Conclusion: The role of village midwives in providing information, encouragement, facilities, and empowering health cadres is crucial in developing local wisdom for stunting prevention.